Africa Dryland Crops Improvement Network - Daudi, Happy M.; Oteng-Frimpong, Richard (Africa Dryland Crops Improvement Network, 2025)
The Africa Dryland Crops Improvement Network (ADCIN), established in August 2023, is a collaborative network initiated after a consultation meeting in Senegal in February 2022 and a network members’ meeting in Ghana in January 2023. It comprises more than 17 countries and over 200 scientists in various agricultural disciplines and organizations. Our vision is to create a dynamic and sustainable network for improving dryland crops in Africa by leveraging and enhancing the collective strengths of its members to accelerate farmers’ access to improved crop varieties.